Green Synthesis of Copper Oxide Nanoparticles Decorated with Borassus flabellifer Leaf Extract for Anti-bacterial and Antioxidant Applications - Prashanthi, Y. (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Nanotechnology has provided a wide range of applications, including copper-containing nanoparticles (CuO NPs) for batteries, gas sensors, superconductors, solar energy conversion, food, pharmaceutical, agriculture, and organic-inorganic nanostructure composites. Materials and Methods: Borassus flabellifer fresh leaves were collected, ground into powder, boiled, centrifuged, and characterised using IR spectra, XRD pattern, TEM analysis and UV-Visible spectrophotometer. The antibacterial and antioxidant properties of CuO NPs were tested using the disc diffusion method, and the DPPH technique was used to calculate the scavenging potential. Results and Discussion: UV-Visible Spectroscopy was used to identify CuO NPs formation and to establish the presence of surface plasmon resonance (SPR). FTIR studies showed the presence of Hydroxyl/amines, C=O Carbonyl/amide groups, alkanes, phenols, carboxylic acid groups, and alcohols. X Zeta potential and TEM analysis were used to verify the size and shape of the produced CuO NPs. Conclusion: Using BF leaf extract, this article describes a green method for producing CuO NPs. CuO NPs were spherical in shape and demonstrated excellent antibacterial activity against both gram-positive and gram-negative bacteria, as well as significant antioxidant activity. These CuO NPs have the potential to be useful tools in biomedical research.